A pilot study investigating the role of 18F‐FDG‐PET in the early identification of chemoradiotherapy response in anal cancer. Issue 4 (30th July 2022) - Smith, Drew; Joon, Daryl Lim; Knight, Kellie; Sim, Jenny; Schneider, Michal; Lau, Eddie; Foroudi, Farshad; Khoo, Vincent
Abstract: Introduction: Anal cancer (AC) is 18 F‐FDG‐PET avid and has been used to evaluate treatment response several months after chemoradiotherapy. This pilot study aimed to assess the utility of semi‐automated contouring methods and quantitative measures of treatment response using 18 F‐FDG‐PET imaging at the early time point of 1‐month post‐chemoradiotherapy. Methods: Eleven patients with AC referred for chemoradiotherapy were prospectively enrolled into this study, with 10 meeting eligibility requirements. 18 F‐FDG‐PET imaging was obtained pre‐chemoradiotherapy (TP1), and then 1‐month (TP2), 3–6 months (TP3) and 9–12 months (TP4) post‐chemoradiotherapy. Manual and semi‐automated (Threshold) contouring methods were used to define the primary tumour on all 18 F‐FDG‐PET images. Resultant contours from each method were interrogated using quantitative measures, including volume, response index (RI), total lesion glycolysis (TLG), SUVmax, SUVmedian and SUVmean . Response was assessed quantitatively as reductions in these measures and also qualitatively against established criteria. Results: Nine patients were qualitatively classified as complete metabolic responders at TP2 and all 10 at TP3. All quantitative measures demonstrated significant ( P  < 0.05) reductions at TP2 for both Manual and Threshold methods. All reduced further at TP3 and again at TP4 for Threshold methods. TLG showed the highest reduction at all post‐chemoradiotherapy time points and classified the most responders for each method at each time point. All patients are recurrence‐free at minimum 4‐year follow‐up. Conclusion: Based on our small sample size, semi‐automated methods of disease definition using 18 F‐FDG‐PET imaging are feasible and appear to facilitate quantitative response classification of AC as early as 1‐month post‐chemoradiotherapy. Early identification of treatment response may potentially improve disease management. Abstract : Anal cancer (AC) is 18F‐FDG‐PET avid and has been used to evaluate treatment response several months after chemoradiotherapy. This pilot study aimed to assess the utility of semi‐automated contouring methods and quantitative measures of treatment response using 18F‐FDG‐PET imaging at the early timepoint of one‐month post‐chemoradiotherapy.